H1‐antihistamines Reduce Progression to Anaphylaxis Among Emergency Department Patients With Allergic Reactions. (June 2017) - Kawano, Takahisa; Scheuermeyer, Frank X.; Gibo, Koichiro; Stenstrom, Robert; Rowe, Brian; Grafstein, Eric; Grunau, Brian
Abstract: Objectives: H1‐antihistamines (H1a) can be used to treat emergency department (ED) patients with allergic reactions; however, this is inconsistently done, likely because there is no evidence that this therapy has an impact on serious outcomes. Among ED patients initially presenting with allergic reactions, we investigated whether H1a were associated with lower rates of progression to anaphylaxis. Methods: This was a retrospective cohort study conducted at two urban Canadian EDs from April 1, 2007, to March 31, 2012. We included consecutive adult patients with allergic reactions while excluding those presenting with anaphylaxis, according to prespecified criteria. The primary outcome was the proportion of patients who subsequently developed anaphylaxis during medical care, either by emergency medical services (EMS) or in the ED. A prespecified subgroup analysis excluded patients who received H1a prior to EMS or ED contact. We compared those who received H1a and those who did not and used multivariable regression and propensity score adjustment techniques to compare outcomes. Results: Of 2, 376 overall patients included, 1, 880 (79.1%) were managed with H1a. Of the latter group, 36 of 1, 880 (1.9%) developed anaphylaxis, compared to 17 of 496 (3.4%) in the non–H1a‐treated group (adjusted odds ratio [AOR] = 0.34, 95% confidence interval [CI] = 0.17–0.70; number needed to treat [NNT] to benefit = 44.74, 95% CI = 35.36–99.67). In the subgroup analysis of 1, 717 patients who did not receive H1a prior to EMS or ED contact, a similar association was observed (AOR = 0.26, 95% CI = 0.10–0.50; NNT to benefit 38.20, 95% CI = 32.58–55.24). Conclusions: Among ED patient with allergic reactions, H1a administration was associated with a lower likelihood of progression to anaphylaxis. These data indicate that early H1a treatment in the ED or prehospital setting may decrease progression to anaphylaxis.